Trans-methylation reactions in plants: focus on the activated methyl cycle - Rahikainen Moona; Alegre Sara; Trotta Andrea; Pascual Jesús; Kangasjärvi Saijaliisa (Wiley-Blackwell Publishing, Inc., 2022)
Trans-methylation reactions are vital in basic metabolism, epigenetic regulation, RNA metabolism, and posttranslational control of protein function and therefore fundamental in determining the physiological processes in all living organisms. The plant kingdom is additionally characterized by the production of secondary metabolites that undergo specific hydroxylation, oxidation and methylation reactions to obtain a wide array of different chemical structures. Increasing research efforts have started to reveal the enzymatic pathways underlying the biosynthesis of complex metabolites in plants. Further engineering of these enzymatic machineries offers significant possibilities in the development of bio-based technologies, but necessitates deep understanding of their potential metabolic and regulatory interactions. Trans-methylation reactions are tightly coupled with the so-called activated methyl cycle (AMC), an essential metabolic circuit that maintains the trans-methylation capacity in all living cells. Tight regulation of the AMC is crucial in ensuring accurate trans-methylation reactions in different subcellular compartments, cell types, developmental stages and environmental conditions. This review addresses the organization and posttranslational regulation of the AMC and elaborates its critical role in determining metabolic regulation through modulation of methyl utilization in stress-exposed plants.